2012
DOI: 10.1093/icvts/ivs263
|View full text |Cite
|
Sign up to set email alerts
|

Does surgical debulking for advanced stages of thymoma improve survival?

Abstract: A best evidence topic in cardiothoracic surgery was written according to a structured protocol. The question addressed was 'Does surgical debulking for advanced stages of thymoma improve survival?' Altogether, only 17 papers were found using the reported search, of which only 10 represented the best evidence to answer the clinical question. The authors, journal, date and country of publication, patient group studied, study type, relevant outcomes and results of these papers are tabulated; these studies have ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 11 publications
2
26
0
Order By: Relevance
“…This issue is of particular relevance when considering that an incomplete resection or debulking procedure could not improve survival relative to biopsy alone, leading to increased recurrence rates and poorer prognosis. 16 In this context, the administration of multimodality therapies has gained growing interest among physicians through the years because of the welldocumented chemoresponsiveness and radioresponsiveness of TTs. With respect to the administration of IT, pioneering experiences were first published in the 1980s by Giaccone and colleagues, 17 and until now few studies and clinical trials on neoadjuvant therapy have been reported in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…This issue is of particular relevance when considering that an incomplete resection or debulking procedure could not improve survival relative to biopsy alone, leading to increased recurrence rates and poorer prognosis. 16 In this context, the administration of multimodality therapies has gained growing interest among physicians through the years because of the welldocumented chemoresponsiveness and radioresponsiveness of TTs. With respect to the administration of IT, pioneering experiences were first published in the 1980s by Giaccone and colleagues, 17 and until now few studies and clinical trials on neoadjuvant therapy have been reported in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…On the basis of the relatively common association of MG and thymoma as shown in our study, we recommend AChR antibody testing on all cats with confirmed or suspected thymoma. This recommendation is standard in human medicine 23, 24…”
Section: Discussionmentioning
confidence: 99%
“…In patients with tumors that appear to be invasive to the great vessels or metastasis to the lymph nodes, a biopsy should be performed prior to the treatment to decide the strategy. We consider that surgical debulking is acceptable for an invasive thymoma, because of the potential for favorable outcome [15]. Thus, all of the patients in the present study had an initial biopsy, which confirmed thymic carcinoma.…”
Section: Commentsmentioning
confidence: 59%